"Good" Places to Work: Women Faculty, Community Colleges, Academic Work, and Family Integration. Issue 179 (4th September 2017) - Ward, Kelly; Wolf‐Wendel, Lisa
Abstract: This chapter draws on a longitudinal study about women faculty, work–family, and career advancement in community colleges. The study found that the participants, though highly satisfied with their careers and qualified for administration, are largely uninterested in moving to more senior administrative positions.